2015
DOI: 10.1155/2015/298378
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphic Variants of miRNA Processing Genes with Larynx Cancer Risk in a Polish Population

Abstract: Laryngeal cancer (LC) is one of the most prevalent types of head and neck cancer. An increasing interest has been focused on the role of microRNA (miRNAs) in LC development. The study group consisted of 135 larynx cancer patients and 170 cancer-free individuals. Nine polymorphisms of pre-miRNA processing genes, DROSHA (rs6877842), DGCR8 (rs3757, rs417309, and rs1640299), RAN (rs14035), XPO5 (rs11077), DICER1 (rs13078 and rs3742330) and TARBP2 (rs784567), were performed by TaqMan SNP Genotyping Assay. It was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…It has been reported that the site of DICER1 rs13078 located in the 3′-UTR of the DICER1 gene and might be an important component in the expression process of the DICER1 gene by influencing the miRNAs binding site, which might impact the DICER1 enzyme's function by DICER1 gene regulation and sequentially impact the expression of microRNAs (52, 60, 61). Additionally, rs13078 genetic variants in DICER1 have been reported to be related to other diseases, such as gestational hypertension (62) and larynx cancer (63).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the site of DICER1 rs13078 located in the 3′-UTR of the DICER1 gene and might be an important component in the expression process of the DICER1 gene by influencing the miRNAs binding site, which might impact the DICER1 enzyme's function by DICER1 gene regulation and sequentially impact the expression of microRNAs (52, 60, 61). Additionally, rs13078 genetic variants in DICER1 have been reported to be related to other diseases, such as gestational hypertension (62) and larynx cancer (63).…”
Section: Discussionmentioning
confidence: 99%
“…RAN is small Ras-related GTP-binding protein that plays an important role in the cell cycle. Specifically, RAN functions in the transport of molecules from the nucleus to the cytoplasm or from the cytoplasm to the nucleus through the nuclear pore complex, in a GTP-dependent manner [42]. In miRNA biology, RAN associates with a protein known as XPO5 to transport pre-miRNA precursors from the nucleus to the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Since they are often located within non-coding regions, their functional significance is not always clear. The discovery of miRs and their ability to bind the 3′-UTR of target genes, is providing a functional explanation of how some SNPs, positioned in non-coding regions, could contribute to cancer susceptibility, with data emerging that miR SNPs are associated with many cancers such as breast cancer [29], gynaecological malignancy [30], lung cancer [31], laryngeal cancer [32], and others. Such genetic variants may alter miR processing and/or target selection, likely contributing to cancer susceptibility and disease progression.…”
Section: Discussionmentioning
confidence: 99%